An ab-initio investigation of novel double halide perovskite Cs2InCoX6(X=F, Cl, Br) materials with direct band structure and broadband light absorption. (December 2022) - Tang, Tian-Yu; Zhao, Xian-Hao; Hu, De-Yuan; Liang, Qi-Qi; Wei, Xiao-Nan; Tang, Yan-Lin
Abstract: In this paper, the electronic, mechanical and optical properties of Cs2 InCoX6 (X = F, Cl, Br) have been studied by first-principle calculation method. The results show that both Cs2 InCoCl6 and Cs2 InCoBr6 are brittle while Cs2 InCoF6 tends to be ductile. Cs2 InCoF6, Cs2 InCoCl6 and Cs2 InCoBr6 are direct bandgap semiconductors with bandgap values of 3.002eV, 1.129eV and 0.865eV, respectively. Compared with other commonly used perovskite materials, Cs2 InCoX6 (X = F, Cl, Br) material has lower effective mass, which is beneficial to improve carrier transport and photoelectric device performance. In addition, Cs2 InCoF6 is more suitable as photodetector and photocatalyst, and the absorption curves of Cs2 InCoCl6 and Cs2 InCoBr6 are well matched with the spectral irradiance of AM1.5. Because Cs2 InCoCl6 has a more suitable band gap, it is a potential candidate for absorbing layer materials in solar cells. Graphical abstract: (a) Cs2 InCoX6 (X = F, Cl and Br) is a stable vacancy ordered double halide perovskite direct band gap semiconductor material.(b) The absorption curves of Cs2 InCoCl6 and Cs2 InCoBr6 match well with the spectral irradiance of AM1.5. Image 1 Highlights: The Cs2 InCoX6 (X = F, Cl, Br) are stable direct bandgap semiconductors with bandgap values of 3.002eV, 1.129eV and 0.865eV, respectively. The absorption curves of Cs2 InCoCl6  and Cs2 InCoBr6 have good match with AM1.5 spectral irradiance. Cs2 InCoCl6 is a good candidate material for solar cell absorption layer.